Enhancing Learning Management in Moroccan Education: Challenges, Opportunities, and Recommendations - Abderrazzak Mazouak; Abdelghani Slassi; Omar ELOuidadi; Mohammed Rehhali; Najoi EL Hazzat (International Journal of Scientific Research and Innovative Studies, 2023)
The Moroccan education system is undergoing a transformative journey with learning management at its core. This research delves into the intricacies of learning management in Moroccan education, deciphering the challenges, recognizing the opportunities, and proposing actionable recommendations. It navigates the landscape of a diverse nation, marked by regional disparities, linguistic richness, and cultural diversity. The challenges encompass inequities in educational access and limited parental involvement, while opportunities arise from the widespread adoption of educational technology and positive student perceptions. The study concludes with recommendations that advocate for policies reducing regional disparities, fostering parental engagement, promoting linguistic inclusivity, optimizing educational resources, and leveraging technology while upholding teacher professional development. This research contributes to the ongoing quest for quality and equity in Moroccan education. Keywords: Learning Management, Moroccan Education, Challenges, Opportunities, Recommendations, Educational Technology, Parental Involvement, Linguistic Diversity, Teacher Professional Development, Educational Equity.